Time Management for Department Chairs - Christian K Hansen (Academic Chairpersons Conference Proceedings, 2019)
In this workshop we discuss time management specifically from the perspective of an academic department chair. Topics covered include management of workflow, prioritizing projects and tasks, delegating effectively, reducing timewasters and using data-centered tools for budgeting and managing time. Participants will have the opportunity to engage in small group discussions using case studies developed based on real-world experiences.
Keywords: Time Management; Leadership; Delegation; Organization; Stress Management